AN INVESTIGATION INTO TRANSLATION OF SENTENCES CONTAINING PARALLELISM IN TRUYEN KIEU FROM VIETNAMESEINTO ENGLISH - NGUYỄN THỊ HƯƠNG LY (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The translation of poetry has always been the central issue for discussion since translation came into being. This research investigated the translation of parallelism in two English versions of Truyện Kiều by Nguyễn Du: The Tale of Kiều by Huỳnh Sanh Thông [52] and Kiều by Micheal Counsell [39]. Basing on the framework by Catford [38] and Newmark [65], this research investigates the similarities and differences between the two versions as well as to generalize the most frequently used procedures in the rendering of parallelisms. The investigation shows that: syntactically, Unit - Shifts is the most procedure and Intra - System - Shifts is the least used procedure in both English versions. Semantically, Literal Translation is the most procedure in The Tale of Kiều by Huỳnh Sanh Thông and Paraphrase is the most procedure used in Kiều by Michael Counsell. Furthermore, the translation by Huỳnh Sanh Thông is closer to the original than the one by Micheal Counsell. Finally, based on the findings and results of the study, some implications for translation, and language teaching and learning are proposed